Distribution and Prevalence of Myxobolus cerebralis in Postfire Areas of Plumas National Forest: Utility of Environmental DNA Sampling. Issue 2 (30th April 2018) - Richey, Christine A.; Kenelty, Kirsten V.; Van Stone Hopkins, Kristina; Stevens, Brittany N.; Martínez‐López, Beatriz; Barnum, Samantha M.; Hallett, Sascha L.; Atkinson, Stephen D.; Bartholomew, Jerri L.; Soto, Esteban
Abstract: Myxobolus cerebralis is a myxozoan parasite and the etiological agent of whirling disease in salmonids. The parasite's life cycle involves waterborne spores and requires both a salmonid fish and the benthic freshwater oligochaete worm Tubifex tubifex (Oligochaeta: Tubificidae). Wildfires can lead to the erosion of fine sediments into stream channels and have been implicated as promoting environmental conditions that are suitable for the survival and success of T. tubifex, whose presence in turn can affect the prevalence of M. cerebralis . Analysis of environmental DNA (eDNA) has the potential to be a powerful tool for evaluating the presence of microorganisms, for which direct observation is impossible. We investigated the presence of M. cerebralis eDNA in river water and river sediment samples collected from areas affected by recent fire activity in Plumas National Forest, California. We compared eDNA loads in the environment to M. cerebralis infection in T. tubifex and sentinel‐exposed Rainbow Trout Oncorhynchus mykiss and the presence of T. tubifex lineages in the same environment. For the latter, we developed a multiplex quantitative PCR assay for detection of T. tubifex lineages I, III, and V. Lineage III T. tubifex and M. cerebralis (eDNA as well as DNA extracted from fish and worm tissues) were detected only in samples obtained from areas affected by the Moonlight wildfire. The association between M. cerebralis infection in sentinel‐exposed fish and eDNA detection in environmental samples only approached significance at a P ‐value of 0.056. However, given the difference in relative effort between the two sampling methods (host versus nonhost environment), our data suggest that eDNA sampling of water and substrate is a promising approach for surveillance of myxozoan fish parasites.